Rasamañjarī : 'Surabhiʼ 'Suṣamā' Saṃskrta-Hindīvyākhyopetā - Bhānudatta Miśra (Śrīharikrṣṇanibandhamaṇimālāyāḥ ; maṇi 4., 1978)
15th century treatise on the Sanskrit poetic considerations about sentiment.